Antioxidant Intake from Fruits, Vegetables and Other Sources and Risk of Non-Hodgkin Lymphoma: The Iowa Women's Health Study - Thompson, Carrie A. (2010)
Antioxidant nutrients found in fruits, vegetables, and other foods are thought to inhibit carcinogenesis and to influence immune status. We evaluated the association of these factors with risk of NHL overall and for diffuse large B-cell (DLBCL) and follicular lymphoma specifically in a prospective cohort of 35,159 Iowa women aged 55–69 years when enrolled at baseline in 1986. Diet was ascertained using a validated semi-quantitative food frequency questionnaire. Through 2005, 415 cases of NHL (including 184 DLBCL and 90 follicular) were identified. Relative risks (RRs) and 95% confidence intervals (CI) were estimated using Cox regression, adjusting for age and total energy. The strongest associations of antioxidants with risk of NHL (RR for highest versus lowest quartile; p for trend) were observed for dietary vitamin C (RR=0.78; p=0.044), α-carotene (RR=0.71; p=0.015), proanthocyanidins (RR=0.70; p=0.0024), and dietary manganese (RR=0.62; p=0.010). There were no associations with multivitamin use or supplemental intake of vitamins C, E, selenium, zinc, copper or manganese. From a food perspective, greater intake of total fruits and vegetables (RR=0.69; p=0.011), yellow/orange (RR=0.72; p=0.015) and cruciferous (RR=0.82; p=0.017) vegetables, broccoli (RR=0.72; p=0.018), and apple juice/cider (RR=0.65; p=0.026) were associated with lower NHL risk; there were no strong associations for other antioxidant-rich foods, including whole grains, chocolate, tea or nuts. Overall, these associations were mainly observed for follicular lymphoma, and were weaker or not apparent for DLBCL. In conclusion, these results support a role for vegetables and perhaps fruits, and associated antioxidants from food sources, as protective factors against the development of NHL and follicular lymphoma in particular.